The spectrum of male breast disease at Charlotte Maxeke Johannesburg Academic Hospital: a 3 year retrospective review - Rattray, Darren (My University, 2024)
Background: The spectrum of male breast disease (MBD) and their relative proportions is not well documented. This study aims to describe the demographics, clinical, radiological and histopathological characteristics of the spectrum of male breast disease managed at Charlotte Maxeke Johannesburg Academic Hospital (CMJAH). Methods: This is a retrospective, descriptive study of all male patients diagnosed with MBD at CMJAH between 1 January 2016 and 31 December 2018. Patients’ data was extracted from the Breast Imaging Department, CMJAH Breast Clinic and the National Health Laboratory Services patients’ records. Data collected included patients’ demographics, clinical presentation, radiological findings and histopathological diagnosis, where available. The collected data was captured using REDCap™ and was analysed using Statistica 13 and SAS version 9.2. P value of 0.05 was used for statistical significance. Results: Of the 269 males imaged, 244 (91%) had a diagnosed breast condition, 90% of which were benign. Gynaecomastia accounted for 85% of all breast disease diagnosed. Patients who presented with benign breast disease were significantly younger than those with malignant breast disease, with a mean age of 45.59 years vs 58.29 years (p = 0.0007). 71% of patients had a known HIV status with 39% being HIV positive. There was a significant association between patients with HIV and benign breast disease (P=0.0129). Conclusion: Gynaecomastia is the most common male breast disease seen at CMJAH. There was a significant association between HIV and benign breast disease. This association should be explored further with respect to the direct effects of the virus and to those of the antiretroviral medication
A research report submitted in partial fulfilment of the requirement for the degree of Master of Medicine (MMed) in in Surgery to the Faculty of Health Sciences, University of the Witwatersrand, School of Clinical Medicine, Johannesburg, 2023
Keywords: Male breast disease (MBD); Gynaecomastia